Keynote Address - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed first, governance and corruption; second, legal and justice system that works; third, financial system to supervise and monitor what is going on in the banks and in the financial sector; and fourth, social system that works to protect people who are out of work, the aged, children, the disabled, and persons that are vulnerable. The leading companies are doing a fantastic job and it is hoped that perhaps with European Institute of Business Administration (INSEAD) can get some leadership in terms of recognition that the future is dependent on peace and social development.